2019
DOI: 10.1007/s10096-019-03619-7
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae outbreak, Southeastern Finland, 2017–2018: molecular epidemiology and laboratory diagnostic lessons

Abstract: This study characterizes a large Mycoplasma pneumoniae outbreak observed in Kymenlaakso in Southeastern Finland during August 2017–January 2018. The first part of the investigation included 327 patients, who sought healthcare consultation at local GPs or hospitals due to clinical symptoms, and were tested for M. pneumoniae antibodies (Patient cohort). The second part of the investigation, conducted approximately 4 weeks after the peak of the outbreak, consisted of school screening of pupils (N = 239) in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…We recently demonstrated that the Mp IgM ASC ELISpot assay differentiates Mp infection from carriage [9]: While Mp DNA and/or IgM were also detected in 48% and 29% healthy control children (n = 21), all were tested negative by the Mp IgM ASC ELISpot assay [9]. Notably, the high Mp detection rate in CAP patients (46%) in this study may be related to the inclusion age of 3-18 years, in which Mp is most frequently detected [1,2], and the coinciding Mp epidemic in Europe during the study period [25][26][27][28]. Prevalence estimates are important for translation of diagnostic study findings into clinical practice.…”
Section: Discussionmentioning
confidence: 63%
“…We recently demonstrated that the Mp IgM ASC ELISpot assay differentiates Mp infection from carriage [9]: While Mp DNA and/or IgM were also detected in 48% and 29% healthy control children (n = 21), all were tested negative by the Mp IgM ASC ELISpot assay [9]. Notably, the high Mp detection rate in CAP patients (46%) in this study may be related to the inclusion age of 3-18 years, in which Mp is most frequently detected [1,2], and the coinciding Mp epidemic in Europe during the study period [25][26][27][28]. Prevalence estimates are important for translation of diagnostic study findings into clinical practice.…”
Section: Discussionmentioning
confidence: 63%
“…M. pneumoniae typically infects children and young adults [ 2 ], and it has been suggested to mainly cause mild and self-limiting respiratory tract infections usually managed by primary health care [ 3 ]. M. pneumoniae is also capable of causing community-acquired pneumonias (CAP) and epidemics in schools, camps, military bases and other communities [ 4 , 5 ]. Although the majority of mycoplasma infections are mild, severe respiratory manifestations may require intensive care unit admissions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting in 2017, an increasing incidence of respiratory infections, including pneumonias, were observed among school-children and their family members in Kymenlaakso region in Southeastern Finland. Testing of respiratory swab and serum samples from 327 individuals by a PCR method [14] and serology, respectively, provided evidence of Mycoplasma pneumoniae infection in 19% of the school-children and their family members [13]. To further investigate the cluster of respiratory infections, respiratory tract swabs from 96 of these individuals (mainly from children) and additional 182 swabs collected from children attending schools in the area were amplified by Chlamydiales-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory swab samples analysed in this study were collected during a M. pneumoniae outbreak observed in Kymenlaakso region in Southeastern Finland during August 2017–January 2018 (as described in detail in [13]). Respiratory tract swab specimens were available from two groups, from a total of 278 individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation